2005
DOI: 10.1111/j.1464-5491.2005.01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the therapeutic approach in pregnancies complicated by borderline glucose intolerance: a randomized clinical trial

Abstract: Even very mild alterations in glucose tolerance can result in excessive or disharmonious fetal growth, which may be prevented by simple, non-invasive therapeutic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 25 publications
(37 reference statements)
4
74
0
1
Order By: Relevance
“…As the 75 g OGCT can be regarded as a surrogate marker of meal postprandial glycaemia [10] , the findings of this study agree with previous findings in that mild elevations in glucose tolerance, or mild dietary glucose elevations within the normal range, may result in increased fetal growth [11] .Patel VN et al conducted a study on 93 pregnant women to monitor longitudinal changes in blood glucose levels in pregnancy and to co-relate it with various maternal and fetal outcomes. They observed that maternal postprandial blood glucose levels affect the birth weight of the baby and also mode of delivery [12] .…”
Section: Discussion and Conclusion:-supporting
confidence: 88%
“…As the 75 g OGCT can be regarded as a surrogate marker of meal postprandial glycaemia [10] , the findings of this study agree with previous findings in that mild elevations in glucose tolerance, or mild dietary glucose elevations within the normal range, may result in increased fetal growth [11] .Patel VN et al conducted a study on 93 pregnant women to monitor longitudinal changes in blood glucose levels in pregnancy and to co-relate it with various maternal and fetal outcomes. They observed that maternal postprandial blood glucose levels affect the birth weight of the baby and also mode of delivery [12] .…”
Section: Discussion and Conclusion:-supporting
confidence: 88%
“…The discrepancy between WHO-GDM prevalence and modified IADPSG-GDM prevalence was highest early in pregnancy. Given the well-documented adverse effects of GDM, early detection may improve maternal and fetal outcomes (37,38,39). The high discrepancy between WHO-GDM prevalence and modified IADPSG-GDM prevalence in early pregnancy in women with PCOS is noteworthy and should be explored further before changing routines.…”
Section: Discussionmentioning
confidence: 99%
“…These subjects were born in 1978/1979 and, at the time, the presence of gestational diabetes was not universally assessed. To overcome the lack of this information in our cohort, we assumed that a subset of LGA subjects born asymmetric (PIO3.1) were likely to be an offspring of diabetic mothers (24).…”
Section: Phenotype Measurementsmentioning
confidence: 99%